SAYOHAT TURIZMIGA OID MATNLARDA MILLIY-MADANIY BIRLIKLARNING LEKSIK-PRAGMATIK XUSUSIYATLARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
A person's thoughts, psyche, and spiritual world are revealed through his speech. A person can express his reaction to everything in existence and events only through his speech. Semantic knowledge can give a person certain thoughts and information about some event or thing. However, this alone is not enough to understand the national and cultural aspects. Taking this into account, this article analyzes some national-cultural units and texts related to the field of tourism in linguistics. In addition, the article also mentions some points about the tourism sector and attention to it. In the process of studying the national-cultural units related to tourism, the importance of the theoretical approach and the appropriateness of using the applied meaning in speech, as well as the issues of their separate system, are discussed.
Keywords: touristic texts, touristic units, speech act, linguistic culture, cultural objects, tourism, pilgrimage tourism, travel, domestic tourism, arch, mosque, madrasa.